2011
DOI: 10.1128/cvi.05027-11
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Inactivated Porcine Circovirus Type 2 (PCV2) Vaccine on PCV2 Virus Shedding in Semen from Experimentally Infected Boars

Abstract: The objective of the present study was to determine the effect of an inactivated porcine circovirus type 2 (PCV2) vaccine on PCV2b virus shedding in the semen of experimentally infected boars by measuring the immunological response and the PCV2b DNA load in blood and semen. Twelve boars were randomly divided into three groups. The boars in group 1 (n ‫؍‬ 4) were immunized with an inactivated PCV2 vaccine and were challenged with PCV2b. The boars in group 2 (n ‫؍‬ 4) were only challenged with PCV2b. The boars i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…A variety of PCV2 vaccines have been developed, such as inactivated vaccines, subunit vaccines and nucleic acid vaccines, etc. [30][31][32][33]. Currently, commercial PCV2 subunit vaccines have been developed on the basis of the PCV2a strain.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of PCV2 vaccines have been developed, such as inactivated vaccines, subunit vaccines and nucleic acid vaccines, etc. [30][31][32][33]. Currently, commercial PCV2 subunit vaccines have been developed on the basis of the PCV2a strain.…”
Section: Discussionmentioning
confidence: 99%
“…The IgG level rose in the vaccinated group indicating that the increase was due to the vaccine and not due to the infection with the PCV2 field virus. Vaccinated piglets are protected against the clinical manifestation of the SD-PCV2 and the load of PCV2 -DNA in organs and tissues including the testes, epididymis and semen is lower than in the unvaccinated groups (Seo et al 2011).…”
Section: Groupsmentioning
confidence: 94%
“…Several commercial PCV2 vaccines are currently available for use in piglets or adult animals, considered to be able to reduce the clinical signs of a PCV2 infection at a farm level. It has also been reported that vaccination against PCV2 in experimentally (Seo et al 2011) or naturally (Alberti et al 2011) infected mature boars can decrease the duration of viral shedding in semen. Since a very high percentage of boars become naturally infected by PCV2 later in life, it is of importance to assess whether the vaccination early in the boar's life with a commercial PCV2 vaccine still has a beneficial effect.…”
mentioning
confidence: 96%
“…Application of the PCV2 vaccine is a key strategy in the prevention and control of PCV2 infection, as it has been determined that clinical signs of PCVAD were reduced under both experimental and field conditions [ 8 , 9 , 10 , 11 , 12 ]. Moreover, finishing pigs vaccinated with PCV2 vaccines experienced a significant increase in average daily gain (ADG) of 41.5 g/day and a significant decrease in mortality rate of 4.4% when compared with pigs of the unvaccinated herds [ 13 ].…”
Section: Introductionmentioning
confidence: 99%